2013
DOI: 10.1111/nph.12226
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transcriptional regulation of GORK channels by superoxide anion contributes to increases in outward‐rectifying K+ currents

Abstract: SummaryIon fluxes are ubiquitous processes in the plant and animal kingdoms, controlled by finetuned regulations of ion channel activity. Yet the mechanism that cells employ to achieve the modification of ion homeostasis at the molecular level still remains unclear. This is especially true when it comes to the mechanisms that lead to cell death.In this study, Arabidopsis thaliana cells were exposed to ozone (O 3 ). Ion flux variations were analyzed by electrophysiological measurements and their transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…Delayed activation of K + outward-rectifying currents was recently evidenced after O 3 -induced oxidative stress leading to programmed cell death (Tran et al, 2013). Thus a new, ROSdependent way of K + channel regulation during oxidative stress was highlighted: molecular experiments revealed that the sustained activation of K + outward currents could follow the unexpected post-transcriptional regulation of guard cell outwardrectifying K + (GORK) channels by O À 2 (Tran et al, 2013).…”
Section: Ion Channels In Guard Cellsmentioning
confidence: 98%
“…Delayed activation of K + outward-rectifying currents was recently evidenced after O 3 -induced oxidative stress leading to programmed cell death (Tran et al, 2013). Thus a new, ROSdependent way of K + channel regulation during oxidative stress was highlighted: molecular experiments revealed that the sustained activation of K + outward currents could follow the unexpected post-transcriptional regulation of guard cell outwardrectifying K + (GORK) channels by O À 2 (Tran et al, 2013).…”
Section: Ion Channels In Guard Cellsmentioning
confidence: 98%
“…Expression profiles revealed that this gene is up-regulated upon the onset of drought, salinity, and cold stress and ABA exposure (Becker et al, 2003;Tran et al, 2013). Reverse genetic evidence further showed that GORK plays an important role in the control of stomatal movements and allows the plant to reduce transpirational water loss significantly (Hosy et al, 2003) and participates in the regulation of salinity tolerance by preventing salt-induced K + loss (Jayakannan et al, 2013).…”
mentioning
confidence: 98%
“…[1][2][3] This consist in an oxidative dependent controlled cell death process involving cell shrinkage due to an early activation of anion channel 1 and a delayed activation of K + outward currents, 2 but also to early events like Ca 2+ influx or singlet oxygen production possibly linked to mitochondrial dysfunction. 1 Here we provide evidence that most of these early events act downstream of caspase-like activities as recently demonstrated for K + channel activation.…”
mentioning
confidence: 99%